Hospital substitute forms of medical assistance during COVID-19 - M. G. Karaylanov; A. V. Mikheev; I. G. Prokin (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2023)
Primary health care in modern socio-economic conditions is given special attention. This type of medical care makes up a large part of the volume of the entire healthcare system in our country, but the least expensive compared to inpatient care. Practically up to 80 % of all available domestic healthcare resources are annually distributed to provide medical care to citizens in stationary conditions. While in modern conditions it is possible to use the available resources more economically and more efficiently. The introduction of hospital-replacing technologies into the practice of medical organizations, both outpatient and inpatient types, is an undoubted advantage of the development of domestic healthcare. During the COVID-19 pandemic, when most of the hospitals are being converted into infectious diseases hospitals, day hospital treatment has become of paramount importance as the main form of hospital-replacing technologies. At the same time, the day hospital is an intermediate link between the outpatient and inpatient networks. Day hospitals in our country appeared relatively recently, but they have received significant development from the standpoint of the greatest medical, social and economic efficiency of treating patients compared to round-the-clock hospitals under the same conditions. During the pandemic, this circumstance was undeniably proven.